ANALISIS PELAYANAN PENGADUAN DAN LAPORAN MASYARAKAT (Studi Kasus di Kepolisian Sektor Dayeuhkolot Wilayah Hukum Kepolisian Resort Bandung) - Harry Anwar (Lembaga Penelitian Universitas Langlangbuana, 2020)
Dayeuhkolot Police Sector Service Center is technically and administratively still faced with limitations. To meet service standards in accordance with Police Chief Skep No.Pol: Kep/22 /VI/2010. This study aims to determine and describe the implementation of the Police Service Center in serving complaints and public reports revealing the factors that influence the task of implementing the Police Service Center and alternative efforts to improve the service of reporting complaints of the community in the Dayeuhkolot police area of ​​the Bandung Police Resort. The research method used is analytical descriptive which describes and analyzes in accordance with what happened to the object of research. The research results show that the Implementation of the Police Service Center in serving and public complaints from the number of reports is relatively high and has not been able to be overcome properly followed by various obstacles such as reports from the community has no clarity (communication), some members of the police are undisciplined, infrastructure means, limited budget and vehicles (resources), there is no clarity from the police regarding reports of loss from the community (disposition), and in receiving reports there are still nonconformities with standards operating procedure.